Perancangan Sistem Autonomous Drone Quadcopter dengan Sistem Waypoint - Taufiqurrohman, Muhammad; Sitepu, Rasional; Widiyanto, Sinung; Ramadhon, Moch. In'am Zayyid (Jurusan Teknik Komputer, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
The development of quadcopter drone technology has progressed rapidly and has been utilized in various fields, including mapping, agriculture, surveillance, and scientific research. In the academic environment, drones play a role not only as objects of study, but also as a medium for learning and developing automated system technology. To support this, a flexible and autonomous drone platform is needed. ArduPilot as an open-source autopilot software, together with the Pixhawk flight controller, is a widely used solution because it supports various features such as waypoint navigation, auto takeoff, and return to launch. The system enables open, modular, and integrative development of UAVs with various sensors. This research aims to design and implement an autonomous quadcopter drone prototype based on ArduPilot and Pixhawk as a means of supporting research and practicum in the campus environment, in order to encourage cross-disciplinary collaboration and readiness to face the industrial era 4.0 and society 5.0.